Study of Hybrid Silica-Polyethyleneglycol Xerogels by Eu3+ Luminescence Spectroscopy - Ribeiro, Sidney José Lima [UNESP]; Dahmouche, K. [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Springer Nature, 1999)
Good optical quality Eu3+-doped silica-polyethyleneglycol hybrids were prepared by the sol-gel process. Thermomechanical analysis showed an increase of the glass transition temperature, due to the stiffness of the polymeric network, as the amount of Eu3+ increased. Europium luminescent properties were used to study structural evolution during the sol-gel transition. For lower doping concentrations dried gels present statistical distributions of Eu3+, typical of an amorphous environment, while for higher concentrations a crystalline-like environment of Eu3+ was observed. A broad emission band was observed in the visible part of the electromagnetic spectrum and assigned to the intrinsic emission from the hybrid polymeric network.
Keywords: Eu3+ spectroscopy; Hybrid gels; Optical probes; Polymer electrolytes; Sol-gel; Crystal structure; Doping (additives); Glass transition; Ionic conduction; Luminescence; Polyelectrolytes; Polyethylene glycols; Sol-gels; Spectroscopic analysis; Thermal expansion; Thermomechanical treatment; Composition effects; Emission spectroscopy; Europium; Luminescence of solids; Stiffness; Optical quality; Spectrofluorimeters; Statistical distributions; Xerogels; Silica; Silica gel